Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T10:40:39+01:00
2)
[(³√8)/2]² = (2/2)² = 1² = 1

[(2√2)/3]² = (2√2)² / 3² = (4*2)/9 = 8/9

[(3√7)/ √6 ]² = (9*7)/6 = 63/6 = 10½

1)
2 * (√3)² = 2*3 = 6

√0,16 = √(16/100) = 4/10 = ⅖

3⁵ * (½)⁵ = (3/2)⁵ = (243/32) = 7 i (19/32)

(3/2)⁻¹ = ( ⅔ )¹ = ⅔

(-1,2)⁻¹ = (6/5)⁻¹ = (⅚)¹ = ⅚
1 5 1
2010-02-24T10:54:08+01:00
1.
2pierwiastek z 3 *pierwiastek z 3 =2*3=6
pierwiastek z 0,16=0,4
3do5 *15 przez 2=243*15/2=18822,5
(1,5)do -2=(3przez2)do-2=(2przez3)do2=4przez9
(-1,2)do -1=(-5przez6)do1=-5przez6

2 w zalaczniku